Factors influence on aggression among football player in Cyberjaya Social League / Muhammad Azhan Azmee - Azmee, Muhammad Azhan (2018)
The purpose of this study were to determine the influences on aggression among football player involve in Cyberjaya Social League (respondent).This study is conducted among respondents who are involve in the social league at Cyberjaya. The respondent was selected using the satrified random sampling technique. By analyze the data, both descriptive and inferential use in this research to identify the main factor of football player aggressiveness and determine the differences in terms of age and type venues for assist researchers the respective hypotheses. The sample of Cyberjaya Social League football player consists of 198 respondents by distribute a questionnaire as instrumentation. This research will be using SPSS version 23.